Efektivitas Lidah Buaya (Aloe Vera) Dan Daunsirih (Piper Betle Linn) Terhadap Kesembuhan Luka Bakar Derajat Ii Pada Tikus Putih (Rattus Norvegicus Strain Wistar) Di Peternakan Tikus Sidomulyo Kediri - Putri Kristyaningsih (coba, 2016)
Background: Second grade burn injuryis burns which includes the destruction of epidermis and upper layers of the dermis and injury in the deeper dermis. Smear use aloe vera and betel leafs, it is an non-pharmacological methods that can accelerate the burn injury healing. Objectives: Determine the effectiveness of aloe vera and betel leafs to the healing of grade II burn injury on white rat in Kediri Sidomulyo livestock. Methods: This research uses a True Experimental, with post test only control group design. The sample in this study were 18 male rats, selected using Sample Random Sampling. Theburns injury made by inducing an iron plate (1x1 cm2) that already heated with boiling water for 5 minutes then stick it on the backs of rat for 30 seconds (area of ​​the epidermis). Data collected using observation sheet, ofusing burn injury woundcare observational sheet. Results: Using ANOVA The results of this study showed that the p value = 0.000, which means that H1 is accepted. Conclusions and Suggestion: There are differences in healing burns secondgrade by using a smear of betel leaf and aloe vera on white rats. This study can be recommended as the development of science in medical-surgical nursing for wound care is more effective and faster in accelerating the healing of burn injury. Key Words :Grade II Of Burn Injury, Aloe Vera, Betel Leafs, White Rats